1-Dimensional confinement of porous polyethylenedioxythiophene using carbon nanofibers as a solid template: an efficient charge storage material with improved capacitance retention and cycle stability - Anothumakkool, Bihag; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (RSC Advances, 2013)
Here, we report a highly conducting porous 1-dimensionally (1-D) confined nano hybrid of polyethylenedioxythiophene (PEDOT) using a cup-stacked hollow carbon nanofiber (CNF) as a solid template for potential charge storage applications. The unique features of the nano confinement involve significantly high porosity and conductivity with the establishment of the 1-D architecture. Since the tubular morphology of the CNF with its open tips provides facile routes for the electrolyte, the overall utilization of the active surface and conductivity increases the charge storage properties of PEDOT in the hybrid. The approach helped in achieving a high specific capacitance of 177 F g(-1) for 40% PEDOT-CNF at a scan rate of 50 mV s(-1) and in retaining 130 F g(-1) even at 3000 mV s(-1) compared to 76 and 30 F g(-1) respectively given by pure PEDOT in 0.5 M H2SO4. The hybrid CP-40 shows a very high power density of 51 kW kg(-1) with an energy density of 4.7 Wh kg(-1). High capacitance retention is supported by the low charge transfer resistance and very low time constant (less than 0.5 s) values for the hybrid using impedance analysis. Phase angle calculations from a Bode plot also show an ideal capacitive nature with -90 degrees phase difference at 0.1 Hz for the hybrids. Apart from all these, the solid CNF backbone helps the hybrid material to display excellent cycle stability with >98% retention in capacitance over 4500 charge-discharge cycles compared to pristine PEDOT at a current density of 2 A g(-1).

Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

Redox-mediated synthesis of functionalised graphene: a strategy towards 2D multifunctional electrocatalysts for energy conversion applications - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Anothumakkool, Bihag; Kurungot, Sreekumar (ChemPlusChem, 2013)
A simple, one-step synthetic route for developing a two-dimensional multifunctional electrocatalyst is reported, by the functionalisation of graphene using oxidised ethylenedioxythiophene (O-EDOT). The mutually assisted redox reaction between graphene oxide (GO) and EDOT facilitates the reduction of GO to graphene with a concomitant deposition of O-EDOT on the surface of the graphene. The oxidised surface of GO catalyses the reaction without using an added reducing agent, so a controlled and uniform deposition of O-EDOT is ensured on the surface of graphene, which essentially prevents the restacking of the layers. UV/Visible, IR, Raman and X-ray photoelectron spectroscopy give valid evidence for the reduction and functionalisation of graphene sheets. The functional groups present on the surface of graphene are found to tune the physical and chemical properties of graphene. Consequently, the functionalised material displays enhanced electrocatalytic activity for the reduction of oxygen to water and I3- to I- relative to pristine graphene. These distinct property characteristics make the material a versatile cathode electrocatalyst for both alkaline anion-exchange membrane fuel cells and dye-sensitised solar cells.
Keywords: electrocatalysts; fuel cells; graphene; redox chemistry; solar cells

Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Layer-separated distribution of nitrogen doped graphene by wrapping on carbon nitride tetrapods for enhanced oxygen reduction reactions in acidic medium - Unni, SreeKuttan M.; Illathvalappil, Rajith; Gangadharan, Pranav K.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Chemical Communications, 2014)
Layer-separated 3D nitrogen doped graphene (NG) with an accessible interstitial surface and modulated activity characteristics for oxygen reduction in acidic medium could be prepared by wrapping NG sheets on in situ generated carbon nitride (CNx) tetrapods.

Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Nitrogen-induced surface area and conductivity modulation of carbon nanohorn and its function as an efficient metal-free oxygen reduction electrocatalyst for anion-exchange membrane fuel cells - Unni, SreeKuttan M.; Bhange, Siddheshwar N.; Illathvalappil, Rajith; Mutneja, Nisha; Patil, Kasinath R.; Kurungot, Sreekumar (SMALL, 2015)
Nitrogen-doped carbon morphologies have been proven to be better alternatives to Pt in polymer-electrolyte membrane (PEM) fuel cells. However, efficient modulation of the active sites by the simultaneous escalation of the porosity and nitrogen doping, without affecting the intrinsic electrical conductivity, still remains to be solved. Here, a simple strategy is reported to solve this issue by treating single-walled carbon nanohorn (SWCNH) with urea at 800 degrees C. The resulting nitrogen-doped carbon nanohorn shows a high surface area of 1836 m(2) g(-1) along with an increased electron conductivity, which are the pre-requisites of an electro catalyst. The nitrogen-doped nanohorn annealed at 800 degrees C (N-800) also shows a high oxygen reduction activity (ORR). Because of the high weight percentage of pyridinic nitrogen coordination in N-800, the present catalyst shows a clear 4-electron reduction pathway at only 50 mV overpotential and 16 mV negative shift in the half-wave potential for ORR compared to Pt/C along with a high fuel selectivity and electrochemical stability. More importantly, a membrane electrode assembly (MEA) based on N-800 provides a maximum power density of 30 mW cm(-2) under anion-exchange membrane fuel cell (AEMFC) testing conditions. Thus, with its remarkable set of physical and electrochemical properties, this material has the potential to perform as an efficient Pt-free electrode for AEMFCs.

Surface-modified single wall carbon nanohorn as an effective electrocatalyst for platinum-free fuel cell cathodes - Unni, SreeKuttan M.; Ramadas, Sarath; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2015)
Platinum (Pt) and its alloys are routinely used in the cathodes of polymer electrolyte membrane fuel cells (PEMFCs) due to their high electrocatalytic activity in oxygen reduction reactions (ORRs). A variety of alternative materials have been examined as alternatives to Pt, but most of these had low activity and their performance deteriorated even further in use. In the present study an alternate electrocatalyst has been examined, obtained by a simple surface modification of single-walled carbon nanohorns by simultaneous doping with Fe and N at 900 degrees C (FeNCNH-900). This had an ORR activity superior to that of 40 wt% Pt on carbon (Pt/C). Compared to Pt/C, FeNCNH-900 gave a 30 mV improvement in onset potential and a 20 mV gain in half-wave potential in an ORR. Its high activity is the result of the simultaneous modulation achieved by the high surface area and the microporosity of carbon nanohorns, together with the establishment of the desired nitrogen-iron coordinated pyrrolic active centres. The catalyst showed excellent electrochemical stability and, most notably, its ORR activity was still increasing after 1000 cycles. Single-cell fuel cell performance using FeNCNH-900 as cathode catalyst showed a maximum power density of 35 mW cm(-2) under alkaline conditions.

Nitrogen and sulphur co-doped crumbled graphene for the oxygen reduction reaction with improved activity and stability in acidic medium - Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2016)
Non-precious dioxygen reduction electrocatalysts have attracted great attention nowadays for the development of stable, cost-effective proton exchange membrane fuel cells. In line with the development of non-precious electrocatalysts, here we report the synthesis of a platinum-free oxygen reduction electrocatalyst based on nitrogen and sulphur co-doped crumbled graphene with trace amounts of iron. The co-doped crumbled graphene structure was obtained by simple oxidative polymerisation of ethylenedioxythiophene in aqueous solution followed by an annealing process under an inert atmosphere. This new electrocatalyst displays improved oxygen reduction activity and electrochemical stability under acidic conditions. The half-cell reaction of the 1000 degrees C annealed polyethylenedioxythiophene (PF-1000) displays only 0.1 V overpotential in both the onset and half-wave potentials compared to state-of-the-art Pt/C in an acidic environment for the ORR. More importantly, the limiting current of PF-1000 clearly surpasses the limiting current displayed by Pt/C, indicating that the crumbled assembly of the graphene flakes helps the system to expose the active sites and the porous network of the material matrix ensures extended accessibility of active sites to the electrolyte and reagent. The dioxygen reduction kinetics of PF-1000 appear similar to those of Pt/C and the system accomplishes the reduction of the dioxygen molecule through the recommended four-electron reduction pathway. The improved activity and electrochemical stability of PF-1000 are mainly attributed to the enriched and well accessible active reaction centres such as graphitic nitrogen, sulphur, and iron coordination and the peculiar morphology of PF-1000. Further, a single cell evaluation of a membrane electrode assembly based on PF-1000 as the cathode catalyst delivered a maximum power density of 193 mW cm(-2) at a cell temperature of 60 degrees C using Nafion as the proton conducting membrane.

Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene

Valorization of coffee bean waste: a coffee bean waste derived multifunctional catalyst for photocatalytic hydrogen production and electrocatalytic oxygen reduction reactions - Unni, SreeKuttan M.; George, Leena; Bhange, Siddheshwar N.; Devi, R. Nandini; Kurungot, Sreekumar (RSC Advances, 2016)
Here, we report the valorization of coffee bean waste (CBW) by producing nitrogen doped porous carbon (p-Cof) having both photocatalytic and electrocatalytic properties using a silica templating method. Morphological investigation of p-Cof reveals the presence of assemblies of highly porous flat carbon blocks. p-Cof exhibits a high surface area (1213 m(2) g(-1)) and a wide range of micro-and mesopores with good electrical conductivity. Along with this, the surface of p-Cof displays the presence of graphitic and pyridone-type nitrogen coordinations, which help p-Cof to perform as a multifunctional catalyst as revealed from its catalytic activities towards photocatalytic hydrogen production (PHP) and electrocatalytic oxygen reduction reactions. p-Cof produces 334 mu mol h(-1) g(-1) of hydrogen from water under visible light and 575 mmol h(-1) g(-1) of hydrogen under solar light irradiation with excellent stability. Along with this, p-Cof also displays improved oxygen reduction reaction (ORR) activity in alkaline medium. A better onset potential (0.91 V vs. RHE) and half-wave potential (0.75 V vs. RHE) are displayed by p-Cof compared to the catalyst derived from the simple annealing of CBW without employing the silica template. Along with the better electrochemical activity, p-Cof shows excellent ORR kinetics and electrochemical stability compared to the current state-of-the-art Pt/C.

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

In situ grown nickel nanoparticles in a calixarene nanoreactor on a graphene-MoS2 support for efficient water electrolysis - Waghmode, Babasaheb J.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Patil, Kashinath R.; Malkhede, Dipalee D. (Sustainable Energy & Fuels, 2017)
Electrochemical production of hydrogen, facilitated in electrolysers, holds great promise for energy storage and solar fuel production. Catalysis of the oxygen evolution reaction (OER) is a bottleneck of this process. However, the sluggish OER kinetics and the utilization of precious metal catalysts are key obstacles in the broad deployment of this energy technology. We report the preparation and use of an inexpensive GrMoS(2)SC(8)Ni nanocomposite material as a highly effective OER catalyst in an alkaline electrolyte. Experimental investigations have shown that improvements can be realized in the catalytic performance of Ni metal if it is a component of the composite material. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises the stabilization of an *-OOH intermediate, which effectively lowers the potential needed for breaking bonds on the surface. Herein, an inexpensive immobilized SC8 layer was used as the nanoreactor to synthesize metallic Ni nanoparticles (NPs) through an in situ redox process. The process was applied to form immobilized NPs on flat and curved 2D surfaces. The outstanding OER performance of Ni NPs could be attributed to their large surface area, efficient mass and charge transport, and high structural stability arising from the unique SC8 cage structure, built on the GrMoS(2) substrate. The GrMoS(2)SC(8)Ni nanocomposite shows the highest activity, exhibiting a 214 mV overpotential at 10 mA cm(-2) (equivalent to 10% efficiency of solarto-fuel conversion) and a Tafel slope of 31 mV dec(-1) in 1 M KOH solution. It further demonstrates high stability as there is no apparent OER activity loss (based on a chronoamperometry test) or particle aggregation (based on SEM image observation) after a 10 h anodization test. The facile preparation method and high efficiency and durability enable this electrocatalyst to be a promising candidate for future large-scale applications in water splitting. Thus, this work opens a new avenue toward the development of highly efficient, inexpensive OER catalysts.

Nitrogen-doped graphene anchored with mixed growth patterns of CuPt alloy nanoparticles as a highly efficient and durable electrocatalyst for the oxygen reduction reaction in an alkaline medium - Illathvalappil, Rajith; Dhavale, Vishal M.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Nanoscale, 2017)
A highly active and durable CuPt alloy catalyst with trigonal bipyramidal and truncated cube-type mixed morphologies, anchored on the nitrogen-doped graphene (NGr) surface (CuPt-TBTC/NGr), was prepared by a simple and fast method. The obtained CuPt alloy showed improved oxygen reduction reaction (ORR) activity, with a 30 mV positive shift in the half-wave potential value, as compared to the state-of-the-art Pt/C catalyst in a 0.1 M KOH solution. The CuPt alloy with the trigonal bipyramidal morphology possesses porous type inter-connected sides, which help to achieve improved mass transport of oxygen during the ORR. The exposure of the (111) plane of the CuPt alloy further improved the catalytic activity towards the dioxygen reduction in alkaline media. The ORR activity of the NGr-supported CuPt alloy was found to be dependent on the reaction time, and improved activity was obtained on the material derived at a reaction time of 90 min (CuPt-TBTC/NGr-90). The material synthesized at a lower or higher reaction time than 90 min resulted in a partially formed trigonal bipyramidal morphology with more truncated cubes or agglomerated trigonal bipyramidal and truncated cubes with closed type structures, respectively. Along with the high intrinsic ORR activity, CuPt-TBTC/NGr-90 displayed excellent electrochemical stability. Even after repeated 1000 potential cycling in a window ranging from 0.10 to 1.0 V (vs. RHE), the system clearly outperformed the state-of-the-art Pt/C catalyst with 15 and 60 mV positive shifts in the onset and half-wave potentials, respectively. CuPt-TBTC/NGr-90 also exhibited 2.1 times higher mass activity and 2.2 times higher specific activity, compared to Pt/C at 0.90 V (vs. RHE). Finally, a zinc-air battery fabricated with the alloy catalyst as the air electrode displayed a peak power density of 300 mW cm(-2), which is much higher than the peak power density of 253 mW cm(-2) obtained for the state-of-the-art Pt/C catalyst as the air electrode.

Single cell fabrication towards the realistic evaluation of a CNT-strung ZIF-derived electrocatalyst as a cathode material in alkaline fuel cells and metal-air batteries - Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Sivasankaran, Vijitha P.; Kurungot, Sreekumar (ChemElectroChem, 2017)
The development of an electrocatalyst possessing all the vital requisites of an ideal electrode material, such as high porosity, high conductivity, and high intrinsic electrochemical activity, holds a decisive key in determining the activity of the triplephase boundary in many energy devices like fuel cells and metal-air battery systems. In the present work, highly porous cobalt-based ZIFs are strung along the highly conducive CNT backbone by using a simple one-pot technique at room temperature, which is then utilized to derive a porous, corrosion-resistant, Co nanoparticle-embedded electrocatalyst. Herein, for the first time, the single cell performance of the Co-ZIF-67-derived electrocatalyst has been evaluated by fabricating membrane electrode assemblies of alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) systems. A maximum power density of 296 mW/cm(2) (vs. 317 mW/cm(2) for 40 wt.% Pt/C) and 60 mW/cm(2) (vs. 64 mW/cm(2) for 40 wt.% Pt/C) in the single cells of ZAB and AEMFC systems, respectively, establishes the practical proficiency of the homemade electrocatalyst for cathode applications during realistic system-level validations.
Keywords: Batteries; Carbon nanotubes; Composite materials; fuel cells; metal-organic frameworks

3-D nanoribbon-like Pt-free oxygen reduction reaction electrocatalyst derived from waste leather for anion exchange membrane fuel cells and zinc-air batteries - Soni, Roby; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Nanoscale, 2019)
Fe-N-x and Fe-S-based ORR electrocatalysts have emerged as rightful candidates to replace Pt in fuel cells to make the technology cheap and sustainable. Fe-N-C catalysts are generally prepared by the pyrolysis of conducting polymers, metal-organic frameworks, aerogels, etc., and the combination of multiple heteroatoms and metal precursors. These precursors are mostly expensive and their synthesis involves multiple steps. In this report, we have demonstrated the synthesis of a Fe-N-C catalyst from the waste leather obtained from the footwear and other leather-consuming industries. The pyrolysis of leather with FeCl3 (metal source) results in the formation of a highly thin and porous nano-ribbon like morphology. Waste leather acts as a cost-free single source of heteroatoms like N, S and carbon. The catalyst synthesized at a temperature of 900 degrees C shows an overpotential of 40 mV and better durability compared to the commercial Pt/C catalyst. The catalyst is demonstrated as the cathode for alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) applications. In the AEMFC, a power density of 50 mW cm(-2) and an OCV of 0.92 V are obtained whereas, in the ZAB, it exhibited a power density of 174 mW cm(-2) compared to 160 mW cm(-2) of the system based on the Pt/C catalyst.

Synthesis of ultrathin PEDOT on carbon nanotubes and shear thinning xanthan Gum-H2SO4 gel electrolyte for supercapacitors - Soni, Roby; Bhange, Siddheshwar N.; Athira, E.; Chetry, Rashmi; Kurungot, Sreekumar (ChemElectroChem, 2019)
Resistance of the electrode material play a vital role for applications in supercapacitors, where lowering the resistance leads to improved performance. Poly(3,4-ethylene dioxythiophene) (PEDOT) possesses high theoretical conductivity; however, the high density of grain boundaries, low accessible surface area, and low rate capability have been pervasive issues affecting the PEDOT-based supercapacitors. To this end, a hydrothermal method is proposed in this work where oxygen functional groups incorporated on the surface of carbon nanotubes (CNTs) are utilized to polymerize 3,4-ethylenedioxythiophene (EDOT). PEDOT forms an ultrathin, well-aligned coating on the surface of CNTs. This arrangement minimizes the number of grain boundaries and increases the electrochemically active surface area. Additionally, a shear-thinning Xanthan gum-H2SO4 gel electrolyte is introduced to overcome the low impregnation of the conventional polyvinyl-based electrolyte due to the hydrophobicity of the CNT-PEDOT composite. A supercapacitor based on this material showed a very low Equivalent Series Resistance (ESR) of 0.31 which leads to a high power density of 74 W cm(-3).
Keywords: gel electrolyte; PEDOT; shear thinning; supercapacitor; xanthan gum

FeNx/FeSx-anchored carbon sheet-carbon nanotube composite electrocatalysts for oxygen reduction - Bhange, Siddheshwar N.; Soni, Roby; Singla, Gourav; Ajithkumar, T. G.; Kurungot, Sreekumar (ACS Applied Nano Materials, 2020)
Even though various Pt-free electrocatalysts for oxygen reduction reaction (ORR) have been introduced, many of them are found to be active only in alkaline conditions. Considering Nafion, phosphoric acid-doped polybenzimidazole (PBI), and so on as the prominent ionomer membranes, used in the commercially available polymer electrolyte membrane fuel cells (PEMFCs), it becomes important that any development on the Pt-free catalysts should ensure the better ORR performance under acidic conditions. The present work effectively tackles this issue, where an ORR-based catalyst could be prepared with simultaneous incorporation of both Fe-N and Fe-S active sites on in situ generated carbon sheets which are spatially separated by the carbon nanotube (CNT) network. This catalyst shows ability to perform under both acidic and basic conditions. This has been achieved by growing a polyethylenedioxythiophene polymer network in the presence of CNT and melamine followed by its pyrolysis under an inert atmosphere. The catalyst formed at 900 degrees C (PMCNT-900) displays 0.94 V onset potential for ORR under acidic electrolyte conditions, which corresponds to 60 mV overpotential compared to its 40 wt % Pt/C counterpart. Interestingly, in single cell demonstration of Nafion-based PEMFC with PMCNT-900 as the cathode catalyst, the system delivered a maximum power density (PD) of 500 and 275 mW/cm(2) at 60 degrees C under H-2-O-2 and H-2-air feed conditions, respectively. On the other hand, in a single cell test in the anion exchange membrane fuel cell (AEMFC) mode, a maximum power density of 65 mW/cm(2) at 50 degrees C could be achieved with the same cathode catalyst, which is a comparable value obtained while employing Pt/C as the cathode. These results, thus, infer to the efficiency of the catalyst to facilitate ORR under the extreme pH conditions, and particularly its performance under acidic condition reveals its prospect as a potential Pt-free electrocatalyst to serve in the Nafion-based systems.
Keywords: carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction; Pt-free ORR

WO3 nanorods bearing interconnected Pt nanoparticle units as an activity-modulated and corrosion-resistant carbon-free system for polymer electrolyte membrane fuel cells - Kumar, Sachin; Bhange, Siddheshwar N.; Soni, Roby; Kurungot, Sreekumar (ACS Applied Energy Materials, 2020)
Commercial platinum-supported carbon (Pt/C) catalyst is the most widely used oxygen reduction reaction (ORR) electrocatalyst in polymer electrolyte membrane fuel cells (PEMFCs). However, carbon oxidation in Pt/C during the operation of PEMFCs poses serious issues, particularly in meeting long-term durability of the cells. Although carbon-free Pt-based catalysts are considered to be the best alternatives, the single-cell performances reported for many such systems are found to be inferior to that of the carbon-based systems. As a practical way to realize a carbon-free electrocatalyst, we have developed a system by dispersing an interconnected Pt nanoparticle network on the nanorods of tungsten oxide (WO3). Uniform dispersion of the WO3 nanorods by fine and more or less interconnected Pt nanoparticles (20 wt %) is a key feature of the electrocatalyst. This has helped the system to achieve an intrinsic ORR characteristics which is very similar to that of Pt/C, as reflected from the comparative analysis of the onset potential, half-wave potential, limiting current density, and the number of electrons transferred in the ORR process. Pt/WO3 also shows better stability under start-stop accelerated potential cycling after 10 000 cycles, compared to Pt/C. The relative decrement in the electrochemically active surface area (ECSA) for Pt/WO3 nanorods was negligible, compared to the similar to 26% decrement registered by Pt/C under the identical testing conditions. Finally, a system-level validation in a single-cell model of PEMFC by fabricating a membrane electrode assembly (MEA) with Pt/WO3 as both the anode and cathode catalyst delivered comparable output power density as that of a similar system fabricated by using Pt/C. ECSA comparison in MEA shows the potential use of Pt/WO3-400 as the catalyst for the fuel cells, since it is exhibiting an ECSA value that is 3.4 greater than that of Pt/C at a Pt loading of 0.5 mg cm(-2).
Keywords: Carbon-free; electrocatalyst; fuel cell; oxygen reduction reaction; tungsten oxide

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene

Facile synthesis of CNT interconnected PVP-ZIF-8 derived hierarchically porous Zn/N co-doped carbon frameworks for oxygen reduction dagger - Singla, Gourav; Bhange, Siddheshwar N.; Mahajan, Mani; Kurungot, Sreekumar (Nanoscale, 2021)
In this work, a strategy has been adopted to construct an architecture through the coordination of polyvinylpyrrolidone (PVP) and a monodisperse zeolitic imidazolate framework (ZIF-8), which was entwined by carbon nanotubes (CNTs) firstly, followed by a pyrolysis process to obtain the hybrid catalyst. The meticulous design of the hybrid material using CNTs to interconnect the PVP assisted ZIF-8 derived porous carbon frameworks together produces a hierarchical pore structure and dual-heteroatom (Zn/N) doping (Zn-N/PC@CNT). Without further acid treatment, the hybrid material prepared after pyrolysis at 900 degrees C (PVP-ZIF-8@CNT-900) has been demonstrated as an efficient non-precious metal catalyst for the oxygen reduction reaction (ORR) with its superior stability compared to the commercial 20 wt% Pt/C catalyst in alkaline media. The catalyst shows better performance towards the ORR, with its more positive onset and half-wave potentials (E-onset = 0.960 V vs. RHE and E-1/2 = 0.795 V vs. RHE) than the counterpart system which is free of both CNT and PVP. The high performance of the hybrid catalyst can be ascribed to the co-existence of dual-active sites with hierarchical pore structures originating from the synergistic effects between Zn/N co-doped porous carbon and CNTs. We further demonstrated the single-cell performance by using the homemade system as the cathode catalyst for the Alkaline Exchange Membrane Fuel Cell (AEMFC) system, which showed a maximum power density of 45 mW cm(-2) compared to 60 mW cm(-2) obtained from the 40 wt% Pt/C catalyst.

Fabrication of a 3D iron-modified NiCo2S4 structure on nickel foam as a bifunctional electrocatalyst for overall water splitting - Singla, Gourav; Mahajan, Mani; Bhange, Siddheshwar N.; Kashyap, Varchaswal (New Journal of Chemistry, 2025)
The development of highly efficient bifunctional electrocatalysts that operate effectively in strong electrolytes, with low overpotentials at defined current densities and excellent durability, has become a central focus in research on overall water splitting. In this study, a three-dimensional (3D) sheet-wrapped wire electrocatalyst, composed of Fe-doped NiCo2S4 on nickel foam (NF), was fabricated. This material demonstrated excellent durability for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline medium. The uniform distribution of Ni, Co, Fe, and S elements significantly enhanced the electro-catalytic performance. The incorporation of Fe improved activity, with the Fe2.5%-NiCo2S4/NF electrocatalyst achieving overpotentials of 310 mV and 260 mV for the HER and OER, respectively, at a current density of 100 mA cm-2. These results were superior to those of both bare nickel foam and NiCo2S4/NF. The 3D configuration facilitated efficient ion transport and contributed to the remarkable catalytic performance. As a water-splitting electrolyzer in an alkaline electrolyte of 1.0 M KOH, the system delivered a current density of 20 mA cm-2 at a cell voltage of 1.66 V, highlighting the effectiveness of this design strategy.